Establishing musculoskeletal oncology service in resource constrained country: challenges and solutions. Issue 11 (December 2017) - Hasan, Obada; Zubairi, Akbar; Nawaz, Zohaib; Umer, Masood
Abstract : The burden of orthopedic tumor surgery in Pakistan is not known. Similarly the number of procedures being performed for bone and soft tissue surgery are not known. This is even becoming more challenging where the existence of rules and regulations in health care are next to minimal. Furthermore data recording in our country and case registries hardly exist. Despite the lack of information and resources, with high disease burden on community, various providers provide surgical interventions every day in our settings. A lot of tumor surgery is still being done by general surgeons and general orthopedic surgeons who have little knowledge and update about musculoskeletal oncology principles. Lack of subspecialized centers and the high cost of such centers force the patients to visit these surgeons for a highly sophisticated problem like a bone tumor which is the disease of young bones. In this article we will emphasize on the difficulty in establishing an orthopedic tumor service in our part of the world and the consequences including delay in diagnosis, faulty course of management and later decline in functionality, disease progression and increased mortality. We will highlight the principles and stepwise approach of orthopedic tumor surgery and explain the difficulty encountered if these principles are not followed.